2013
DOI: 10.1007/s40279-013-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity-Related Injuries in Older Adults: A Scoping Review

Abstract: The purpose of this project is to conduct a comprehensive and systematic scoping review to identify and document the breadth of literature related to physical activity-related injuries in older adults. The population of interest was adults (both males and females) over the age of 65 years, participating in exercise, leisure-time, or sport-type physical activities. The initial search yielded 16,828 articles, with 43 articles ultimately included. The final 43 articles utilized the following study designs: three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 57 publications
0
23
0
1
Order By: Relevance
“…In general, it is easy to assume that older athletes are at higher risk of activity-related injuries when compared to their younger counterparts. However, attempts at determining their actual incidence of injury have shown that they appear to be at similar risk (Ganse et al, 2014;Stathokostas et al, 2013). Recently, more attention has been directed towards the study of the mature athlete with specific attention to knee injuries.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is easy to assume that older athletes are at higher risk of activity-related injuries when compared to their younger counterparts. However, attempts at determining their actual incidence of injury have shown that they appear to be at similar risk (Ganse et al, 2014;Stathokostas et al, 2013). Recently, more attention has been directed towards the study of the mature athlete with specific attention to knee injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Os valores de lesão encontrados no presente estudo podem ter sido semelhantes, pois mesmo que o desporto seja praticado de forma não competitiva, pode, ainda, existir o caráter competitivo. Apesar disso, estudo de revisão sistemática sobre lesões em idosos não sugere que esses indivíduos apresentem um risco aumentado de lesão da participação em atividades físicas de lazer (34) . Na verdade, a forte evidência dos benefícios de saúde de atividades físicas para uma população idosa supera a não participação, à luz do momento pequeno risco de lesão (34) .…”
Section: Discussionunclassified
“…Physical activities from overall population groups are a usual apprehension, but increasing levels of recreational physical activities and sports involvements have been informed in some population groups [2,[5][6][7]. However, the promotion of physically active lifestyles to reduce the risk of chronic diseases should consider the possible problem of accompanying injuries [3,8,9]. Injuries are practically the unique disadvantage of exercise or sport, but may be a usual outcome from physical activities and have been disclosed as a sizable problem [5][6][7]10].…”
Section: Introductionmentioning
confidence: 99%